The Female Body as a Site of Patriarchal Power Play: - Liton Chakraborty Mithun (Crossings)
The female body has been a gendered space upon which patriarchy plays out its power dynamics. The making, re-making and unmaking of the female body has remained a subject to wishes and whims of men. In most cases, women are denied agency and freedom over their bodies. Men have exerted their power on the female body in the form of subjugation, repression, oppression, and exploitation.Hence, rape and all forms of sexual assault on women and girls in the context of a war can be considered a patriarchal tool to assert the dominance of the attacking party and demoralize the community under attack. The victims of sexual attacks undergo psychological trauma during and after the war. In this context, Tarfia Faizullah’s debut collection of poems Seamappears as a feminist investigation into the narrative of rape victims of the Bangladesh Liberation War. This book lends voice to the rape victims of the 1971 war whose bodies were politicized by the androcentric Pakistani army. Through a feminist lens, this qualitative paper will endeavor to explore how the female body served as a site of patriarchal domination in the Bangladesh Liberation War in the light of Seam.